Improving Two-Layer Data Security in Image Steganography - Kaur, A; Kaur, J (International Journal of Computer Sciences and Engineering, 2025)
In this paper, two security layers are added on the data using cryptography and steganography algorithms. The data is encrypted using lightweight RECTANGLE algorithm. Next, the data is hiding is done using steganography algorithm. In the steganography scheme, the edges of the cover image are determine using Canny Edge detection technique which can extract inclusive range of edges. Further, worked on theory of color which plane is more suitable for maximum/minimum data hiding. The encrypted data is splitted into 3:2:3 ratio and hide in the edges of the RGB plane simultaneously. The performance analysis is done based on PSNR and embedding capacity. The experimental results show that the Improved technique is secure, consume lesser area, less embedding capacity, and provide high PSNR. Further, data extraction is possible without communicating any extra information with stego image